My friend uses a wheelchair - Chang, Kirsten, 1991- (All kinds of friends., 2020)
"In My Friend Uses a Wheelchair, beginning readers are introduced to different characters who use wheelchairs, how using a wheelchair may affect their actions, and how we can be good friends to people who use wheelchairs." --